STRATEGI PEMBINAAN MENTAL MASYARAKAT DALAM MENGHADAPI RADIKALISME - Arini Indah Nihayaty; Bagong Suyanto (Universitas Islam Negeri Mataram, 2020)
This study analyzes the dynamics of religion-based radicalism in Indonesia. It also describes how government carries out mental development for the community to prevent radicalism. The purpose of this study is to determine the roots of religious-based radicalism that occurs in Indonesia. Also to determine the government's strategy in dealing with the problem of radicalism, especially in the field of mental development. This study is expected to provide a solution for this complex situation. Moreover, religious-based radicalism often leads to acts of terrorism. This study uses a qualitative method with a literature review approach. Literature sources used, both those obtained from within the online and printed ones. Data analysis techniques are carried out based on three stages, namely, reduction, presentation, and drawing conclusions. The results of this study indicate that the dynamics of radicalism in Indonesia are related to the global terrorist movement. The government has carried out prevention and counter strategy against terrorism. Some are in the form of community mental development programs. The others are in the form of repressive measures. Prevention and eradication of religious-based radicalism requires the active role of all community exponents. This study is expected to enrich scientific research in the field of mental development, dealing with the harm religious-based radicalism in society.